2016
DOI: 10.54386/jam.v18i2.944
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on rice yield at Jorhat, Assam

Abstract: Impact of climate change on rice yield variabilities under various Representative Concentration Pathways (RCPs) has been estimated for Jorhat district, under Upper Brahmaputra Valley Agroclimatic Zone of Assam. CERES-Rice module of DSSAT 4.5 was calibrated and validated for rice cultivar ‘Mahsuri’ under three different dates of transplanting between May and July. Increase in both maximum and minimum temperatures at Jorhat, under all the RCPs for 2020, 2050 and 2080, suggests increasing level of heat stress dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Mandal and Singha (2020 reported that yield variability of summer rice reduced with the rise in daily average temperature up to 20.74 • C and beyond. Goswami et al (2016) found that the vulnerability of rice cultivation to the impacts of projected temperature rise varied with sowing/transplanting time and the variety grown. Summer rice seedlings grown under future projected temperature conditions were found to exhibit stunted growth with a reduction in root lengths and biomass as well as reduced physiological activity (Rehman and Tanti, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandal and Singha (2020 reported that yield variability of summer rice reduced with the rise in daily average temperature up to 20.74 • C and beyond. Goswami et al (2016) found that the vulnerability of rice cultivation to the impacts of projected temperature rise varied with sowing/transplanting time and the variety grown. Summer rice seedlings grown under future projected temperature conditions were found to exhibit stunted growth with a reduction in root lengths and biomass as well as reduced physiological activity (Rehman and Tanti, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Mid-season drainage/ alternate wet and dry method of irrigation is reported to reduce methane emissions from rice fields (Manjunath et al, 2009;Li et al, 2018;Surendran et al, 2021;Win et al, 2021). Techniques such as adjustment of sowing time, double transplanted rice, direct seeded rice, aerobic rice, and System of Rice Intensification (SRI) are found to be effective in sustaining rice production in a changing climate (Goswami et al, 2016;Uphoff and Thakur, 2019;Mandal and Singha, 2020;Assefa et al, 2021).…”
Section: Climate-induced Hazard Mitigation and Adaptation Strategies ...mentioning
confidence: 99%
“…The expected effect of climate change includes increase in temperature and uncertainties in rainfall. Goswami et al (2016) examined the precise effects of climate change on rice yield variability for the Jorhat district of Assam under various Representative Concentration Pathways (RCPs), and found that the projected grain yield variances over the observed mean yield from 2009 to 2013 ranged from -12.7 to -43.4 percent under all the scenarios and dates of transplanting under study. Bhuvaneswari et al (2014) investigated the impact of climate change on rice in the western zone of Tamil Nadu using DSSAT-CERES crop simulation model and stated that the yield is anticipated to decrease under future warmer climatic circumstances and that the rice crop would be significantly impacted by the changing climate.. Ding et al (2020) reported that changing sowing date is a better tactic that deals the climate change effect in China.…”
mentioning
confidence: 99%